On the non-chiral intermediate long wave equation. (4th August 2022) - Berntson, Bjorn K; Langmann, Edwin; Lenells, Jonatan
Abstract: We study integrability properties of the non-chiral intermediate long wave equation recently introduced by the authors as a parity-invariant variant of the intermediate long wave equation. For this new equation we: (a) derive a Lax pair, (b) derive a Hirota bilinear form, (c) derive a Bäcklund transformation, (d) use, separately, the Bäcklund transformation and the Lax representation to obtain an infinite number of conservation laws.